Development of a New and Improved Guanidine-based Rac1 Inhibitor with in Vivo Activity against Non-Small Cell Lung Cancer - Ciarlantini, Matias Sebastián (2020)
Rac1 (Ras-related C3 botulinum toxin substrate 1), is a member of the family of Rho GTPases involved in the dynamic control of cytoskeleton reorganization and other fundamental cellular functions including growth, motility and survival. Aberrant activity of Rac1 and its regulators is common in human cancer. In particular, deregulated expression/activity of Rac Guanine nucleotide Exchange Factors (GEFs), responsible for Rac activation, has been largely associated to a metastatic phenotype and drug resistance. Thus, the development of novel Rac1-GEF interaction inhibitors is a promising strategy for finding new preclinical candidates. In this work, we have studied structure-activity relationships within a new family of N,N’-disubstituted guanidine as Rac1-GEF protein-protein interaction inhibitors, starting from our first developed member 1A-116. We found that new analogue 1D-142, bearing a pyridine ring instead of benzene ring, presents improved antiproliferative activity in human cancer cell lines and higher potency as Rac1-GEF interaction inhibitor in vitro. In addition, 1D-142 reduces TNFα-induced NF-κB nuclear translocation, a mechanisms mediated by Rac1 during cell proliferation and migration in NSCLC. Notably, 1D-142 was used to show for the first time the application of a Rac1 inhibitor in a lung cancer animal model.